2016
DOI: 10.1007/s10549-016-3967-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of mitogen-activated protein kinases (MAPK) in breast cancers

Abstract: BackgroundMitogen-activated protein kinases (MAPKs) are signalling transduction molecules that have different functions and diverse behaviour in cancer. In breast cancer, MAPK is related to oestrogen receptor (ER) and HER2.MethodsProtein expression of a large panel of MAPKs (JNK1/2, ERK, p38, C-JUN and ATF2 including phosphorylated forms) were assessed immunohistochemically in a large (n = 1400) and well-characterised breast cancer series prepared as tissue microarray. Moreover, reverse phase protein array was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
2
21
0
1
Order By: Relevance
“…This study showed that nuclear MAPK1/3 phosphorylation was associated with better outcome, especially in tamoxifen-treated cases. All these immunohistochemical studies in large cohorts of (luminal) breast cancer specimens confirm in part our in silico findings in relation to PIK3CA mutation [18] and our TMA findings that nuclear MAPK1/3 phosphorylation correlates with favorable outcome [16] , [17] . Future prospective studies are needed to verify above retrospective findings and to establish MAPK1/3 phosphorylation as biomarker.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study showed that nuclear MAPK1/3 phosphorylation was associated with better outcome, especially in tamoxifen-treated cases. All these immunohistochemical studies in large cohorts of (luminal) breast cancer specimens confirm in part our in silico findings in relation to PIK3CA mutation [18] and our TMA findings that nuclear MAPK1/3 phosphorylation correlates with favorable outcome [16] , [17] . Future prospective studies are needed to verify above retrospective findings and to establish MAPK1/3 phosphorylation as biomarker.…”
Section: Discussionsupporting
confidence: 86%
“…The other study demonstrated a trend between tamoxifen response and MAPK1/3 phosphorylation [15] . Additionally, nuclear and cytoplasmic MAPK1/3 phosphorylation were also studied in large well-characterized breast cancer series to investigate its biological and clinical significance [16] , [17] . This study showed that nuclear MAPK1/3 phosphorylation was associated with better outcome, especially in tamoxifen-treated cases.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, MAPKs are associated with good prognosis across most classifications of breast cancer, notably in those with positive ER. 154 …”
Section: Mitogen-activated Protein Kinasementioning
confidence: 99%
“…Furthermore, the function of MAPKs is affected by their cross talk and interaction with other pathways, which can influence their behavior. 154 …”
Section: Mitogen-activated Protein Kinasementioning
confidence: 99%
“…Using MOSTWAS and iCOGs summary-level GWAS statistics for breast cancer-specific survival [36], we identified 11 survival-associated loci that are enriched for p53 binding and oxidoreductase activity pathways [66,67]. These loci include two genes (MAP3K6 and MAP4K5 ) encoding mitogen-activated protein kinases, which are signaling transduction molecules involved in the progression of aggressive breast cancer hormone subtypes [68]. TWAS using MOSTWAS models was able to recapitulate 5 out of 14 known…”
Section: Discussionmentioning
confidence: 99%